MarCell™ software for modeling bone marrow radiation cell kinetics - Hasan, J. S.; Jones, T. D.; Morris, M. D. (Medical physics (Lancaster), 1997)
Differential equations were used to model cellular injury, repair, and compensatory proliferation in the irradiated bone marrow. Recently, that model was implemented as MarCell™, a user-friendly MS-DOS computer program that allows users from a variety of technical disciplines to evaluate complex radiation exposure. The software allows menu selections for different sources of ionizing radiation. Choices for cell lineages include progenitor, stroma, and malignant, and the available species include mouse, rat, dog, sheep, swine, burro, and man. An attractive feature is that any protracted irradiation can be compared with an equivalent prompt dose (EPD) in terms of cell kinetics for either the source used or for a reference such as 250 kVp x rays or 60 Co . EPD is used to mean a dose rate for which no meaningful biological recovery occurs during the period of irradiation. For human as species, output from MarCell™ includes: risk of 30-day mortality; risk of whole-body cancer and leukemia based either on radiation-induced cytopenia or compensatory cell proliferation; cell survival and repopulation plots as functions of time or dose; and 4-week recovery following treatment.